Phytoconstituents, Nutritional Value, UV and IR Spectra of Extracts and Dyes from Bixa orellana Seeds, Sorghum bicolor Stalks, and Parkia biglobosa Peels - Alio Sanda, Mahamadou Djibrilla; Badu, Mercy; Boadi, Nathaniel; Djika, Hachimou; Awudza, Johannes (Journal of Tropical Pharmacy and Chemistry, 2025)
The increasing consciousness about the usefulness of renewable and biodegradable source of materials, plants-based precursors for products development are preferred against synthetic sources mostly because of fear of adverse effect and source extinction. In this study, the dietetic and biological characteristics of raw materials from Bixa orellana (Achiote), Sorghum bicolor (Sorghum) and Parkia biglobosa (Dorowa) were investigated. The results showed phytochemical compounds such as alkaloids, flavonoids, tannins, coumarins, sterols, triterpenoids, saponins, anthraquinones and anthocyanin with functional groups such as carbonyl, hydroxyl and nitrogenous groups confirmed by the FTIR results while UV spectroscopy showed absorption within visible light.  Sorghum stalks presented the highest amount of crude fiber content (31.138% ±1.15) whereas the peels of Dorowa were the richest sample in carbohydrate content (82.209%) and the seeds of Achiote contained the highest amount of protein (14.805% ±0.12) and lipids (2.339%). Isolating necessary chemical components could lead to drug, food and paint development.